Functional Outcomes After Percutaneous Nephrostomy in Hydronephrotic Kidneys in Adult Population (Bangladesh Journal of Urology, 2020)
Objective: To evaluate the results of renal function after percutaneous nephrostomy in hydronephrotic kidneys in adult population.Methods: This study was performed on 57 patients of more than 18 years of age with hydronephrosis due to PUJ obstruction and split renal function